(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Concrete reinforced by short steel fibres is typical brittle matrix composite, in which fibres are impeding cracks growth, such way increasing material’s tensile strength. The use of steel fibre reinforced concrete (SFRC) in structures with high physical and mechanical characteristics makes possible to reduce their weight and cost, to simplify their production technology, to reduce or eliminate reinforcement labour, at the same time increasing reliability and durability. Randomly distributed discontinuous fibres are bridging the crack’s flanks providing material’s “ductility”- like non-linear behaviour at cracking stage. The current study is focused on one formulation of a specific type of concrete matrix with added fibres and without fibres. Concrete cubes and prisms without fibres and having in every situation the same content of 60 mm long fibres were fabricated. Cubes (100×100×100 mm) were tested in compression and beams (100×100×400 mm prisms) were tested under four-point bending (4PBT). Fracture process (crack growth) in the material was modelled, based on experimental results (part of experimental data was used). Finite element method (FEM) using the ANSYS program analysis were realized modelling stress distributions in the broken beams with the goal to predict fracture process. Model’s prediction was validated.